Digital Learning Management in Madrasahs: Models, Implementation and Evaluation - Simbolon, Maruli; Patimah, Siti; Warisno, Andi; Murtafiah, Nurul Hidayati; Gani, A. (International Journal on Advanced Science, Education, and Religion, 2025)
The digital transformation of Islamic educational institutions, particularly madrasas, requires a structured approach to managing technology-based learning that remains aligned with Islamic values. This study aims to analyze the models, implementation, and evaluation of digital learning management in madrasas by identifying best practices and existing challenges. The method used is a literature review that examines research findings and scientific publications from the last seven years related to digital learning management, Islamic educational management, and technology integration in educational settings. The results indicate that digital learning management in madrasas has evolved through integrated models combining LMS utilization, blended learning approaches, and Islamic value integration; implementation strategies highly dependent on infrastructure readiness, teacher competence, and institutional policy support; and evaluation processes increasingly driven by digital data for more accurate decision-making. The study concludes that effective digital learning management requires synergy among technological readiness, teacher digital competence, school leadership, and the reinforcement of Islamic moral values ​​within the digital ecosystem, ensuring that digitalization enhances learning quality without diminishing the spiritual identity of Islamic education